BELAJAR DALAM PERSPEKTIF AL-QUR’AN - Marisa Hannum Harahap; Alwizar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Learning is a complex process that occurs in every person throughout his life. The learning process occurs because of the interaction between a person and his environment. Therefore, learning can happen anytime and anywhere. One sign that a person has learned is a change in behavior in that person which may be caused by a change in the level of knowledge, skill or attitude.